Therapeutic potential of alternative splicing in cardiovascular diseases - Jun Cao; Ziyu Wei; Yu Nie; Hou-Zao Chen (EBioMedicine, 2024)
Summary: RNA splicing is an important RNA processing step required by multiexon protein-coding mRNAs and some noncoding RNAs. Precise RNA splicing is required for maintaining gene and cell function; however, mis-spliced RNA transcripts can lead to loss- or gain-of-function effects in human diseases. Mis-spliced RNAs induced by gene mutations or the dysregulation of splicing regulators may result in frameshifts, nonsense-mediated decay (NMD), or inclusion/exclusion of exons. Genetic animal models have characterised multiple splicing factors required for cardiac development or function. Moreover, sarcomeric and ion channel genes, which are closely associated with cardiovascular function and disease, are hotspots for AS. Here, we summarise splicing factors and their targets that are associated with cardiovascular diseases, introduce some therapies potentially related to pathological AS targets, and raise outstanding questions and future directions in this field.